A KNOWLEDGE, ATTITUDE AND PRACTICE PERSPECTIVE STUDY ON THE AWARENESS OF DENGUE FEVER AMONG INTERNS OF A TERTIARY CARE HOSPITAL IN CHENNAI. - DR.T. JANAGAN.M.D; DR.S.A.SRIDEVI. M.D (International Journal of Pharma and Bio Sciences, 2016)
Dengue fever (DF) is increasingly recognized as one of the world’s major vector borne diseases and causes significant morbidity & mortality in most tropical and subtropical countries of the world. It has also became the most common arbo viral diseases of human. Dengue fever is endemic in most parts of India and continues to be a public health concern. WHO currently estimates that there may be 50–100 million dengue infections world wide. The objective of this study is to determine the level of knowledge, attitude and practice among the interns. A cross sectional study among the interns of the tertiary care hospital was carried out during the month of October 2015. A pre structured and self-administered questionnaire was distributed and the data regarding the knowledge, attitude and practice regarding dengue fever were collected. The data collected were statistically analysed using the SPSS statistical software.